Energy, Exergy and Exergo-Economic Analysis of an OTEC Power Plant Utilizing Kalina Cycle - Basta, Giuseppe; Meloni, Nicoletta; Poli, Francesco; Talluri, Lorenzo; Manfrida, Giampaolo (Global Journal of Energy Technology Research Updates, 2021)
This study aims to analyse an Ocean Thermal Energy Conversion (OTEC) system through the use of a Kalina Cycle (KC), having a water-ammonia mixture as a working fluid. KC represents a technology capable of exploiting the thermal gap of ocean water. This system was then compared with OTEC systems, which exploit ammonia, R134A and butane-pentane mixture as working fluid. The comparison was carried on through energy analysis, exergetic analysis, and exergo-economic analysis using the EES (Engineering Equation Solver) software. For each case study, cost rates and auxiliary equations were evaluated for all components and the mass flow rate and unit exergy cost for each stream. The results showed that the KC with water-ammonia as working fluid achieves the best exergo-economic performance among the examined cycles. The cost of electricity produced through KC using water - ammonia mixture was found to be 26,66 c€/kWh. The thermal efficiency and the exergetic efficiency were calculated and the withdrawal depth of ocean water was considered. The efficiencies resulted to be 3.68% for the thermal efficiency and 95.96% for the exergetic efficiency.